Effects of hydrogen annealing temperature on the resistive switching characteristics of HfOx thin films. (December 2018) - Jung, Yong Chan; Seong, Sejong; Lee, Taehoon; Kim, Seon Yong; Park, In-Sung; Ahn, Jinho
Abstract: We investigated the effects of hydrogen annealing temperature on Pt/HfOx /Pt resistive switching memory devices. Memory devices annealed in a hydrogen environment exhibited unipolar resistive switching behaviors with low set, reset, and forming voltages owing to reduction of the HfOx film by the injected hydrogen. The devices annealed at 400 °C exhibited good endurance, lasting 7 times as long as non-annealed device. This improvement could be attributed to the generation of more oxygen vacancies in HfOx, which resulted in more conducting pathways forming during the resistive switching process. The devices annealed in the hydrogen environment also showed longer retention times than those of non-annealed devices. Therefore, hydrogen annealing improves the performance of this nonvolatile switching memory by enabling low power operation at lower operation voltages with greater reliability.